Sistema de gestión de la rentabilidad de proyectos para la empresa Noux C.A - Pilatuña Caizatoa, Elvis Enrique (2017)
The NOUX C.A. Company is a strategic information management institution which works making project of business intelligence, SAP support and training and Teradata tools. By the projects number developed by the company, it is necessary to take an adequate management control. Doing the monitoring process to ensure the profitability of each one, the Financial Management has available information in excel files but the process is deficient because the information on projects and their costs on several occasions are not update. So that this research consists of corporate computer system development focused on the Web by JAVA language programming, using the J2EE technology on frameworks JSF, EJB, JPA and PRIMEFACE in order to allow to the company keeps track project that are developed into it and determine the profitability that was generated for each one. System designing and development will use the agile development methodology, SCRUM, because it will help to have a follow up the project development. In addition, the project helped to define the modules which are: Administration, project and profitability....